(untitled) (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2025)
Balinese Usadha has long been recognized as a traditional herbal healing system, yet its philosophical and spiritual dimensions embedded in ancient lontar manuscripts remain underexplored. This study aims to examine the structure of Tantric teachings and the concept of transcendence in Usadha texts as a form of practical philosophy in Balinese life. Employing a qualitative-exploratory approach and philosophical hermeneutics, this research analyzes texts such as Usadha Jagra, Usadha Bhuta, and Raja Nala, supported by interviews with traditional healers. The findings reveal that Usadha healing addresses not only the physical body but also facilitates a spiritual process of self-awareness through ritual symbolism, mantra, and ethical-spiritual practices. Tantric teachings are evident in the body-energy structure, cosmic duality, and meditative disciplines embedded within healing acts. This study affirms that Usadha Bali is a rich source of philosophical knowledge, offering significant contributions to contemporary discourse on spirituality, ecological education, and holistic healing practices.